2 - Assistance and Conflict: The African Diaspora and Africa’s Development in the Twenty-first Century - Erhagbe, Edward O. (Africa Development, 2007)
Africans in the diaspora contributed laudably to the socio-political liberation of Africa, especially in the southern Africa sub-region. A discernable feature of their involvement in Africa’s political liberation efforts was that they tended to work within the boundaries of ‘the agreed agenda’ of African peoples and governments. With the liberation of South Africa, there has now been an obvious shift in the main agenda of ‘African Liberation’. The emphasis now seems to be on democratisation and the socioeconomic development of Africa. However, the differences of opinion and the conflictive nature of the new programmes of focus require some pertinent questions, in order to chart a realistic, workable and less confrontational agenda and modus operandi for diaspora and continental African co-operation in the years ahead. Among other things, this paper sets in a clear historical perspective the varied ways Africans in the diaspora contributed to Africa before now. It also highlights the shift from the ‘political liberation theology’ to ‘developmental theology’. Considering the rather sensitive and complex issues of national sovereignty, integrity and interventionism, the paper explores whether there is still a basis for diaspora Africans continuing their ‘interference’ in African internal business; who should set the agenda for their involvement; and how should they be involved. A fundamental conclusion of the paper is that the cooperation of diaspora and continental Africans is important in fostering Africa’s development. Nevertheless, such a cooperation should respect the national sovereignty and integrity of African nations and peoples. Consultation and cooperation, rather than antagonism or confrontation between the two groups, stand as the viable and workable option.